Volume 5: 19th Biennial Conference on Mechanical Vibration and Noise, Parts A, B, and C 2003
DOI: 10.1115/detc2003/vib-48563
|View full text |Cite
|
Sign up to set email alerts
|

2:2:1 Resonance in the Quasiperiodic Mathieu Equation

Abstract: In this work, we investigate regions of stability in the vicinity of 2:2:1 resonance in the quasiperiodic Mathieu equation: d2xdt2+(δ+εcost+εμcos(1+εΔ)t)x=0, using two successive perturbation methods. The parameters ε and μ are assumed to be small. The parameter ε serves for deriving the corresponding slow flow differential system and μ serves to implement a second perturbation analysis on the slow flow system near its proper resonance. This strategy allows us to obtain analytical expressions for the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…In (9), are the components of the total moment applied to the rotor, and are the principal components of the rotor moment of inertia tensor, with (10) , for a perfectly symmetric rotor. 2 It is worth noting that the rotor is driven into a sinusoidal oscillation whose amplitude is typically 0.08 (rad) while the tilt angles and and the bounce motion are limited by the gap between the rotor and the substrate, which means that .…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (9), are the components of the total moment applied to the rotor, and are the principal components of the rotor moment of inertia tensor, with (10) , for a perfectly symmetric rotor. 2 It is worth noting that the rotor is driven into a sinusoidal oscillation whose amplitude is typically 0.08 (rad) while the tilt angles and and the bounce motion are limited by the gap between the rotor and the substrate, which means that .…”
Section: Equations Of Motionmentioning
confidence: 99%
“…The assumption that the bounce motion is prescribed is valid because, theoretically, one can adjust by varying the electro-magnetic field between the rotor and Equation (41) is a quasiperiodically driven Mathieu equation with cubic nonlinearity and external forcing. This equation has been extensively studied [7]- [10] for the case of no substrate motion, that is, when . In [7], it is shown that in the nonlinear Mathieu equation, one obtains finite-amplitude motion, which may be quasiperiodic or chaotic, due to the nonlinear resonance in contrast to the linear Mathieu equation where instability implies unboundedness.…”
Section: Remarks On the Effects Of Parametric Excitation On The mentioning
confidence: 99%
“…This treatment yields a global analysis for the existence and bifurcation of QP motions near the resonant curve lying in the largest instability region. Note that in Rand et al [3], analytical approximations to this largest instability region near 2:2:1 resonance were obtained for the linear QP Mathieu Equation (2).…”
Section: Introductionmentioning
confidence: 98%
“…This represents the 2:2:1 resonance case. Analytic expressions for the transitions curves separating stable and unstable regions were obtained in Rand et al [3] by using a double perturbation method valid for small ε and μ. In particular, the analytic approximation of the transition curves bounding the largest of the local instability regions near δ = 0.25 and ω = 1 in Equation (1) were obtained in the form…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation